MAKNA HATI KUDUS YESUS BAGI MASYARAKAT MODERN MENURUT DOKUMEN DILEXIT NOS - Oswin Wowor; Longginus Sikteubun (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2026)
Human living in the modern world that are increasingly losing the deep meaning of the heart. Modern humans who are increasingly losing their hearts are shown from various phenomena and conflicts that occur in this day. Phenomena and conflicts that occur in the modern world such as poverty, consumer culture, egoism and so on show that the world is increasingly losing its heart. The heart is the deepest center of the existence of living beings that connects the soul and body. Meanwhile, the Sacred Heart of Jesus is the center that leads every person to salvation through compassion aimed at the world. The deep union between the human heart and the Divine heart opens a door that has so far blocked sincere love between fellow human beings, especially those who are marginalized. The encounter of our hearts with the Sacred Heart of Jesus unites us with others, healing the wounds that arise from ourselves and others. His Sacred Heart also strengthens us to be able to love and serve our brothers and sisters.